2017
DOI: 10.1039/c7py00055c
|View full text |Cite
|
Sign up to set email alerts
|

Photo-responsive thiol–ene networks for the design of switchable polymer patterns

Abstract: Photo-patternable thiol–ene networks are prepared by combining versatile o-NBE chemistry with the distinctive advantages of a typical “click” reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…It was shown that the curing of the monomers with o ‐NBE groups proceeds either upon deep UV or visible light exposure without inducing a premature photoisomerization of the o ‐NBE links. By combining versatile o ‐NBE chemistry with the salient features of a photoinduced “click” reaction, photopolymers were synthetized by the visible‐light induced step‐growth reaction between multi‐functional thiols and an alkene‐terminated o ‐NBE monomer . The spatially controlled cleavage of the thiol‐ene networks enabled the fabrication of defined relief structures by mask illumination.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the curing of the monomers with o ‐NBE groups proceeds either upon deep UV or visible light exposure without inducing a premature photoisomerization of the o ‐NBE links. By combining versatile o ‐NBE chemistry with the salient features of a photoinduced “click” reaction, photopolymers were synthetized by the visible‐light induced step‐growth reaction between multi‐functional thiols and an alkene‐terminated o ‐NBE monomer . The spatially controlled cleavage of the thiol‐ene networks enabled the fabrication of defined relief structures by mask illumination.…”
Section: Introductionmentioning
confidence: 99%
“…(2‐nitro‐1,4‐phenylene) bis(methylene) acetate (vinyl‐NBE) was synthesized as reported in previous work. [ 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…The photosensitive thiol‐ene network formed by the visible light induced click reaction between trimethylolpropane tris(3‐mercaptopropionate) (TMPMP) and vinyl‐NBE ((2‐nitro‐1,4‐phenylene) bis(methylene) acetate) was prepared according to literature (Figure S1, Supporting Information). [ 21 ] The formation of the network was confirmed by means of fourier‐transform infrared spectroscopy spectra, which were taken before and after the curing reaction. As described in detail in the Supporting Information, the thiol‐ene reaction occurs simultaneously by step‐growth reaction between the thiol moieties and vinyl double bonds.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations